Penerapan Model Pembelajaran Picture and Picture dalam Pembelajaran di Sekolah Minggu - I Putu Ayub Darmawan; Diana Kristanti (Regula Fidei: Jurnal Pendidikan Agama Kristen, 2020)
Sunday School is a forum for education in the church which is held with the aim of fostering members of the congregation. The learning process in Sunday school needs to continue to innovate so that the message of the Bible can be well understood. To help Sunday school children understand the Bible's message, one of the lessons that can be applied is a cooperative learning model picture and picture. The author then conducted a qualitative study to examine the application of picture and picture in learning in Sunday school. The results showed that the application of picture and picture can help increase the ability to listen and retell through sorting according to the storyline. Abstrak Sekolah Minggu adalah wadah pendidikan dalam gereja yang diselenggarakan dengan tujuan untuk membina anggota jemaat. Proses pembelajaran di sekolah minggu perlu terus berinovasi sehingga pesan Alkitab dapat dipahami dengan baik. Untuk membantu anak-anak sekolah minggu memahami pesan Alkitab, salah satu pembelajaran yang dapat diterapkan adalah cooperative learning model picture and picture. Penulis kemudian melakukan penelitian kualitatif untuk mencermati penerapan picture and picture dalam pembelajaran di sekolah minggu. Hasil penelitian menunjukkan bahwa penerapan picture and picture dapat membantu peningkatan kemampuan menyimak dan menceritakan kembali melalui pengurutan gambar sesuai alur cerita.